Beckman O2 & CO2 Analyzer - Dietrich, T. A. (1964)
Beckman's Space Engineering Group (SEG) was formed within the Scientific Process Instruments Division (SPID) in 1959. It developed instrumentation for use in the punishing environmental conditions of space as well as, in the case of this instrument, under the sea.
Keywords: Scientific apparatus and instruments; Oxygen--Measurement; Carbon dioxide; Water--Dissolved oxygen; Oceanographic instruments; Beckman Instruments, Inc.; Oxygen--Analysis